Curvature in the very-high energy gamma-ray spectrum of M 87 - Aharonian, Felix A.; Ait Benkhali, Faical; Aschersleben, J.; Ashkar, H.; Backes, M.; Martins, V. Barbosa; Batzofin, R.; Becherini, Y.; Berge, D.; Bernlöhr, Konrad; Böttcher, M.; Boisson, C.; et al. (Astronomy and astrophysics, 2024)
The radio galaxy M 87 is a variable very-high energy (VHE) gamma-ray source, exhibiting three major flares, which were reported in 2005, 2008, and 2010. Despite extensive studies, the origin of the VHE gamma-ray emission is not yet fully understood. In this study, we investigate the VHE gamma-ray spectrum of M 87 during states of high gamma-ray activity, utilizing 20.2 h of H.E.S.S. observations. Our findings indicate a preference for a curved spectrum, characterized by a log-parabola model with extra-galactic background light (EBL) model above 0.3 TeV at the 4σ level, compared to a power-law spectrum with EBL. We investigate the degeneracy between the absorption feature and the EBL normalization and derive upper limits on EBL models that are mainly sensitive in the wavelength range of 12.4 μm-40 μm.